2000
DOI: 10.7164/antibiotics.53.714
|View full text |Cite
|
Sign up to set email alerts
|

Kynapcin-12, a New p-Terphenyl Derivative from Polyozellus multiplex, Inhibits Prolyl Endopeptidase.

Abstract: A major histopathological hallmark of Alzheimer's disease (AD) is the presence of amyloid deposits in the parenchyma of the amygdala, hippocampus, and neocortex1}. The principal component of the amyloid is the /3-amyloid protein (A/?), a 39-43 amino acid peptide composedof a portion of the transmembrane domain and the extracellular domain of the amyloid precursor protein (APP)2). The neurotoxicity of the A/3 has been detected in several cell systems, including primary cultured neurons3). The A/3 having an alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Drugs having capacity to scavenge ROS may have the potential to delay its manifestation (Zhao & Zhao, 2013) and may prove immensely effective in treating the condition. Identifying the PEP inhibitors having therapeutic effect against amnesia and dementia highlights the need to analyze novel PEP inhibitors Diderot et al, 2005;Lee & Song, 2000). Based on our literature survey on bioactivities of lichens, it was found that lichens and their metabolites are reported for their medicinal value and therapeutic potential in a number of diseases and health problems, except PEP inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs having capacity to scavenge ROS may have the potential to delay its manifestation (Zhao & Zhao, 2013) and may prove immensely effective in treating the condition. Identifying the PEP inhibitors having therapeutic effect against amnesia and dementia highlights the need to analyze novel PEP inhibitors Diderot et al, 2005;Lee & Song, 2000). Based on our literature survey on bioactivities of lichens, it was found that lichens and their metabolites are reported for their medicinal value and therapeutic potential in a number of diseases and health problems, except PEP inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…A Korean research group investigated the EtOAc soluble fraction of the mushroom and reported the chemical structure of two active compounds, thelephoric acid (76) and kynapcin-9 (77) with their PEP activities [178]. Another p-terphenyl derivative, named kynapcin-12, having PEP inhibitory activity with an IC 50 value of 1.25 µM, was isolated by Lee and collaborators from a methanolic extract [179]. The correct chemical structure of kynapcin-12 (78) was later assigned by total synthesis [180].…”
Section: Polyozellus Multiplex (Underw) Murrillmentioning
confidence: 99%
“…The biological activities of isolated compounds had also been investigated. Kynapcin-12, a p-terphenyl derivative, and kynapcin-13 and -28 belonging to benzofuran skeleton, showed propyl endopeptidase inhibitory activities [16,17]. In addition, polyozellin enhanced quinone reductase and glutathione S-transferase activities, which prevent from chemical carcinogenesis in hepa1c1c7 cells [18].…”
Section: Introductionmentioning
confidence: 99%